1974
DOI: 10.1083/jcb.62.1.104
|View full text |Cite
|
Sign up to set email alerts
|

PROPHASING OF INTERPHASE NUCLEI AND INDUCTION OF NUCLEAR ENVELOPES AROUND METAPHASE CHROMOSOMES IN HELA AND CHINESE HAMSTER HOMO- AND HETEROKARYONS

Abstract: Fusing human HeLa metaphase cells with HeLa interphase cells resulted within 30 min in either of two phenomena in the resultant binucleate cell: either prophasing of the interphase nucleus or formation of a normal-appearing nuclear envelope around the metaphase chromosomes. The frequency of either occurrence was strongly dependent on environmental pH. At pH's of 6.6 8.0, prophasing predominated; at pH 8.5 nuclear envelope formation predominated. Additionally, the frequencies of the two events in multinucleate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 14 publications
5
15
0
Order By: Relevance
“…Some of these characteristics distinguish them from the mitotic factors (40). The pH dependency ofthese factors is also in agreement with the results of the early cell fusion experiments of Obara and co-workers (21)(22)(23), which suggested that high pH favored "telophasing" and low pH "prophasing" or premature chromosome condensation . Our own studies (Hittelman and Rao, unpublished data) show that the frequency of premature chromosome condensation induction is much higher if a low pH is maintained during the collection of mitotic cells and subsequent fusion procedures.…”
Section: Discussionsupporting
confidence: 87%
“…Some of these characteristics distinguish them from the mitotic factors (40). The pH dependency ofthese factors is also in agreement with the results of the early cell fusion experiments of Obara and co-workers (21)(22)(23), which suggested that high pH favored "telophasing" and low pH "prophasing" or premature chromosome condensation . Our own studies (Hittelman and Rao, unpublished data) show that the frequency of premature chromosome condensation induction is much higher if a low pH is maintained during the collection of mitotic cells and subsequent fusion procedures.…”
Section: Discussionsupporting
confidence: 87%
“…TLN were more frequently found in polykaryons containing many interphase nuclei. This observation conforms to earlier finding that low metaphase/ interphase ratio in fused cells promotes nuclear membrane formation around metaphase chro mosomes (Obara et al 1974). Significant increase in the number of TLN up to 1.5hr incuba tion period is most probably due to membrane formation around metaphase chromosomes originated from asynchronic prophase nuclei.…”
Section: Resultssupporting
confidence: 80%
“…The results of the above-cited experiments can be favorably compared to those obtained in cell-fusion studies using mitotic chromosome condensation (PCC) in a n interphase nucleus depends largely on the ratio of mitotic to interphase nuclei at the time of fusion (see Adlakha and Rao, 1987). After multiple fusion of several cells in G, phase with one metaphase cell, metaphase chromosomes decondense and a nuclear membrane starts to form around them (Obara et al, 1974). This process has been termed "telophasing," due to its resemblance to events in normal telophase.…”
Section: Nucleo-cytoplasmic Relationships Duringmentioning
confidence: 99%